Tubularized and Effaced Gastric Cardia Mimicking Barrett Esophagus Following Sleeve Gastrectomy: Protocolized Endoscopic and Histological Assessment With High-resolution Manometry Analysis. Issue 1 (12th July 2022) - Johari, Yazmin; Budiman, Kenny; Catchlove, William; Laurie, Cheryl; Hebbard, Geoffrey; Norden, Sam; Brown, Wendy A.; Burton, Paul
Abstract : Objective: To describe expected endoscopic and histological changes at gastro-esophageal junction (GEJ) and define diagnostic paradigms for Barrett esophagus (BE) postsleeve gastrectomy (SG). Summary Background Data: De novo incidence of BE post SG was reported as high as 18.8%. A confounding factor is the lack of standardized definition of BE post SG, which may differ from the general population due to procedure-induced alterations of GEJ. Methods: Part 1 involved evaluating endoscopic changes of GEJ post SG (N = 567) compared to pre SG (N = 320), utilizing protocolized preoperative screening, postoperative surveillance and synoptic reporting. Part 2 involved dedicated studies examining causes of altered anatomical and mucosal GEJ appearance using histopathology (N = 55) and high-resolution manometry (HRM) (N = 15). Results: Part 1 – A characteristic tubularized cardia segment projecting supra-diaphragmatically was identified and almost exclusive to post SG (0.6% vs.26.6%, P < 0.001). True BE prevalence was low (4.1%pre SG vs. 3.8%post SG, P = 0.756), esophagitis was comparable (32.1% vs. 25.9%, P = 0.056). Part 2 - Histologically-confirmed BE was found in 12/55 patients, but 70.8% had glandular-type gastric mucosa implying tubularized cardia herniation. HRM of tubularized cardia demonstrated concordance of supra-diaphragmatic cardia herniation between endoscopy and HRM (3 cm vs. 3.2 cm, P = 0.168), with frequent elevated isobaric intraluminal pressurizations in supra-and infra-diaphragmatic cardia compartments. Conclusion: A novel appearance of tubularized cardia telescoping supra-diaphragmatically with flattening of gastric folds is common post SG, likely associated with isobaric hyper-pressurization of proximal stomach. incidence of true BE post SG is low in short-intermediate term. These provided a clear framework for approaching endoscopic screening and surveillance, with correct anatomical and mucosal identifications, and clarified key issues of SG and BE.